Biopori Absorption Hole: Alternative Technology in the Framework Simple Harvest Rain Water Conservation. - Purnami, Wahyuni (STKIP Santu Paulus Ruteng, 2016)
Water supply is a necessity for the prolongation of life. Water supply should be keptand conserved in order to meet the necessity of all the living things which are continously growing anddeveloping. Manggarai region, especially in Ruteng, tends to have high rain precipitation. Yet, it is nowonderthat in the dry season there is a draught, while flood and landslide occur in the raining season. It is a timefor raining to be harvested for the sake of water preservation and the prevention of flood and landslide. Asimple technology can be applied by creating the Biopori Absorption Hole (BAH). Biopori AbsorptionHole is a rain harvesting technology which optimally uses microorganism to make the land’s pores for theexpansion absorption facet to be absorbed into the ground. In addition to the benefit for the water-landpreservation, Biopori Absorption Hole is also useful for recyclinghousehold organic wastes and themaking of compost that can raise high economic value.Keywords: biopori, technology, harvest rain, water conservation